Contributions to the educational and cultural community. Summative evaluation of a collaborative experience in the Museumof Lleida - Parisi-Moreno, Verónica; Llonch Molina, Nayra (Pulso. Revista de educación, 2017)
This work is part of a larger research that consists of the summative evaluation of an educational proposal implemented in the Museum of Lleida. This proposal arises from the involvement of the museum in a project promoted by the Network of School Libraries of the regions of Lleida. The objective of the research is to provide empirical evidence on the degree of satisfaction of the school public with the proposal, the impact on the learning process of the students and the degree of achievement of the objectives pursued by both institutions. To this end, an evaluative research has been carried out using the quantitative, nonexperimental and descriptive method. The results obtained, among others, guarantee the benefit of the museum adapting its resources to the needs of the environment. The research opens new ways for museums to contribute to the educational and cultural community of the environment, which allows them to be able to run as an institution focused on the global needs of the community. of contexts of social interaction linked to heritage